Hotels’ reactions to environmental changes: The example of Antalya Hotels - Ömüriş, Ece; Dirlik, Onur (International Journal of Contemporary Economics and Administrative Sciences, 2020)
The aim of this study is to try to understand how hotels, one of the main economic actors in the tourism sector, react to their environment in order to ensure sustainability in the face of environmental changes. Especially in Turkey, it is important to ensure the sustainability of tourism. However, one of the biggest obstacles in ensuring sustainability is the crisis. Because tourism is among the most vulnerable industries to crises such as an economic recession. In this study, qualitative research methods were used to seek responses to research questions, have interviewed twenty-three hotel senior employees in the center of Antalya. Findings show that when the environment changes rapidly hotels reduce costs and downsize, have a low potential to create an alternative in the face of possible changes, and have lack of practices of cooperation and acting as a union. Also, findings show that public authorities’ reactions are insufficient.